Study of a TLP motions and forces using 3D source technique (Journal of Naval Architecture and Marine Engineering, 2019)
The production and consumption of oil and other petroleum products have been increasing rapidly over the years, which led to the scarcity of easily retrieved oil due to urbanization. As a result, oil producers are motivated to go to deeper ocean to extract oil and other resources.Offshore platforms in deep water like TLPs are used for exploration of oil and gas from under Seabed and processing. But it is challenging to design precisely such type of giant structure in deep sea as it experiences huge forces, motion and other environmental loads which are non-linear, need sophisticated solution techniques and expensive to apply. In the present study wave exciting forces and motions of free floating TLP are carried out in frequency domain analysis using three dimensional source distribution techniques within the scope of linear wave theory where six degrees of freedom have been considered. The same geometrical data are used as an input to HydroStar, which is based on linear wave theory. Results obtained from both the programs are compared which shows a good agreement and also validated with the published results. Comparison of heave motion with and without tether are illustrated where it can be easily understood the effect of tendon. Forces and motions prediction of TLP is emphasized which has been done precisely in the present work and in future it will help us to design the TLPs as well as the tendon system in deep sea. Finally, a number of recommendations have been made for further research based on the present study.